Bacterial endotoxin-induced maternal inflammation leads to fetal intestinal injury and affects microbial colonization in the neonatal period. (12th December 2022) - Huang, Qingmei; Lu, Siliang; Zhu, Yunlei; Wei, Bingmei; Chen, Yujun; Bai, Faming
Abstract: Background: Intraamniotic infection is associated with an increased risk of multiple adverse outcomes in offspring, especially neonatal necrotizing enterocolitis (NEC), which is one of the serious gastrointestinal diseases in neonates. However, the underlying mechanism remains undefined. We hypothesize that bacterial endotoxin-induced maternal inflammation causes intestinal injury in offspring, thereby affecting the composition of the intestinal microbiome. Methods: Pregnant Sprague Dawley rats were received intraperitoneal injections with 700 μg/kg lipopolysaccharide (LPS, which was the same as bacterial endotoxin) or saline at 15 days of gestation. Pups were allowed to deliver naturally and euthanized at days 0, 3 and 7 after birth. Intestinal tissue and feces samples from offspring were collected to evaluate the effects of maternal inflammation on intestinal flora colonization and intestinal mucosal development. Results: Significant intestinal injury of the offspring induced by prenatal LPS exposure was observed on day 0 and 3 after birth. In addition, prenatal LPS exposure also induced significant changes in the intestinal microbiome of the offspring with a significant increase in Proteobacteria ( Escherichia-Shigella ) and a decrease in Firmicutes at 7 days after birth. Conclusions: Thus, our findings suggest that LPS-induced maternal inflammation induces intestinal injury in offspring and subsequently leads to NEC-like changes in the composition of the intestinal microbiome.